Changing medical relationships after the ACA: Transforming perspectives for population health. (December 2016) - Franz, Berkeley A.; Skinner, Daniel; Murphy, John W.
Abstract: American health care has undergone significant organizational change in recent decades. But what is the state of core medical relationships in the wake of these changes? Throughout ACA-era health care reform, the doctor–patient relationship was targeted as a particularly important focus for improving communication and health outcomes. Recent developments however have shifted the focus from individual-level outcomes to the wellbeing of populations. This, we argue, requires a fundamental rethinking of health care reform as an opportunity to renegotiate relationships. For example, the move to population medicine requires that the very concept of a patient be resituated and the scope of relevant relationships expanded. Medical relationships in this era of health care are likely to include partnerships between various types of clinicians and the communities in which patients reside, as well as a host of new actors, from social workers and navigators to scribes and community health workers. To address the upstream determinants of population health, providers must be increasingly willing and trained to collaborate with community stakeholders to address both medical and non-medical issues. These community-based partnerships are critical to providing health care that is both relevant and appropriate for addressing problems, and sustainable. Approaching health care reform, and the focus on population health, as a fundamental reworking of relationships provides scholars with a sharper theoretical lens for understanding 21st century American health care. Highlights: This article explains why and how medical relationships are changing in response to health policies such as the Affordable Care Act and the more general transition to population health. To successfully undertake population health initiatives, medical educators, policy makers, and health care practitioners need to conceptualize the new medical relationships that are required in population health. Policymakers should consider how changing medical relationships require changes in how and where we train medical students